Effect of Emodin on Preventing Postoperative Intra-Abdominal Adhesion Formation. (2nd August 2017) - Wei, Guangbing; Wu, Yunhua; Gao, Qi; Zhou, Cancan; Wang, Kai; Shen, Cong; Wang, Guanghui; Wang, Kang; Sun, Xuejun; Li, Xuqi
Abstract : Background . Postoperative intra-abdominal adhesions are a major complication after abdominal surgery. Although various methods have been used to prevent and treat adhesions, the effects have not been satisfactory. Emodin, a naturally occurring anthraquinone derivative and an active ingredient in traditional Chinese herbs, exhibits a variety of pharmacological effects. In our study, we demonstrated the effect of emodin treatment on preventing postoperative adhesion formation. Materials and Methods . A total of 48 rats were divided into six groups. Abdominal adhesions were created by abrasion of the cecum and its opposite abdominal wall. In the experimental groups, the rats were administered daily oral doses of emodin. On the seventh day after operation, the rats were euthanized, and blood and pathological specimens were collected. Abdominal adhesion formation was evaluated by necropsy, pathology, immunohistochemistry, Western blot, and enzyme-linked immunosorbent assay analyses. Results . Abdominal adhesions were markedly reduced by emodin treatment. Compared with the control group, collagen deposition was reduced and the peritoneal mesothelial completeness rate was higher in the emodin-treated groups. Emodin had anti-inflammatory effects, reduced oxidative stress, and promoted the movement of the intestinal tract (P < 0.05 ). Conclusion . Emodin significantly reduced intra-abdominal adhesion formation in a rat model.